Vasectomy as Social Assistance Policy Discourse: A Normative Juridical Analysis from Ibn ʿUthaymīn’s Fatwa - Akhmad Husaini; Marwan Mas'ud; Goliz Cahyadi; Sylvano Wijaya Aji Pratama (Universitas Nurul Jadid, 2026)
This research examines the normative and ethical implications of the West Java Governor’s statement proposing vasectomy as a prerequisite for prioritizing social assistance, by addressing the central question of whether such policy discourse constitutes a violation of maqāṣid al-syarīʿah and generates legal–ethical conflicts within Islamic and national legal frameworks. Employing a qualitative approach with library-based research methodology, this study analyzes secondary data through descriptive and content analysis. The analytical framework is grounded in maqāṣid al-syarīʿah theory, while conclusions are drawn using a deductive reasoning approach. The findings demonstrate that conditioning social assistance on vasectomy represents a normative inconsistency that contradicts the principle of preserving progeny (ḥifẓ al-nasl), as articulated in Ibn al-ʿUthaymīn’s fatwas, which prohibit permanent sterilization except in cases of medical necessity. Furthermore, the study identifies significant legal and ethical tensions, including the erosion of religious commitment, distortion of the concept of tawakkul, and violations of bodily autonomy and reproductive rights as protected under national law and human rights norms. The research concludes that such policy discourse risks producing structural injustice against economically marginalized groups. As an alternative, this study proposes rights-based and maqāṣid-oriented solutions, including sustainable economic empowerment programs, comprehensive reproductive health education, voluntary use of non-permanent contraception, and the reinforcement of a fair, non-discriminatory social security system to achieve public welfare without compromising fundamental religious values and human rights.